2009
DOI: 10.2478/s11535-009-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Planting of different-sized tree transplants on arable soil

Abstract: Abstract:On the arable land of the Rosovka Stream alluvium in the Czech Republic, a windbreak containing native woody species, was planted within a restoration project. This study evaluates the effect of that planting of three different tree sizes, on the rate of growth. The sizes of transplants employed in this study included small (1.0 -1.5 meters tall), medium-sized (2.0 -2.5 meters tall) and large (with a trunk circumference of 0.1-0.12 meters). The following native tree species, from the Eurosiberian regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…This shows that the use of saplings with trained crowns is not justified in terms of the long-term development of the stand. This was confirmed in other biocorridors (Jelínek & Úradníček, 2010b), and the same conclusion was reached by Dostálek et al (2009Dostálek et al ( , 2014.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This shows that the use of saplings with trained crowns is not justified in terms of the long-term development of the stand. This was confirmed in other biocorridors (Jelínek & Úradníček, 2010b), and the same conclusion was reached by Dostálek et al (2009Dostálek et al ( , 2014.…”
Section: Discussionsupporting
confidence: 78%
“…Such research included the influence of the stand establishment method and transplant size on subsequent tree growth. The monitoring was carried out at the Valová and Klapý site (Dostálek et al, 2007(Dostálek et al, , 2009(Dostálek et al, , 2014. Occasionally, other components of these biocorridors or other components of the TSES were monitored for students' final theses (Prokešová, 2019;Slach, 2014;Šimečková, 2010;Šťastová, 2012;Vašíček, 2015;Večeřa, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Griffin et al (2010) and Shober et al (2010) tracked xylem water potential to determine tree establishment in a high summer rainfall climate. Here, we showed that stomatal sensitivity to root loss is amplified by high ET o (Hipps et al, 2014) on transplanted trees with higher leaf area:root ratio (Dostalek et al, 2009;Riikonen et al, 2011). Stomatal closure mediates root loss and dry to moderate xylem water tension enough that water potential is not a good measure of root establishment following transplanting in dry climates.…”
Section: Resultsmentioning
confidence: 90%
“…Higher g S per unit leaf area would mean less isohydric stress, more carbon uptake that would explain the leap in growth Year 2. This growth surge highlights smaller trees being more effective in re-establishing a new root: leaf area balance than BB and BR-Large trees (Dostalek et al, 2009;Watson, 2005). BR tree root systems have the advantage of more direct root contact with ambient soil.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation